2021
DOI: 10.3390/cells10102662
|View full text |Cite
|
Sign up to set email alerts
|

The Review of Bioeffects of Static Magnetic Fields on the Oral Tissue-Derived Cells and Its Application in Regenerative Medicine

Abstract: Magnets have been widely used in dentistry for orthodontic tooth movement and denture retention. Nevertheless, criticisms have arisen regarding the biosafety of static magnetic field (SMF) effects on surrounding tissues. Various controversial pieces of evidence have been discussed regarding SMFs on cellular biophysics, but little consensus has been reached, especially in the field of dentistry. Thus, the present paper will first review the safe use of SMFs in the oral cavity and as an additive therapy to ortho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 89 publications
1
18
0
Order By: Relevance
“…According to the strength of the magnetic field, SMF can be classified as a hypomagnetic field (HyMF, <5 μT, commonly found in outer space), weak SMF (5 μT–1 mT, such as a geomagnetic field), moderate SMF (1 mT–1 T, such as common permanent magnets), and high SMF (>1 T, such as MRI and superconducting magnet) [ 47 ]. Numerous studies have shown that SMFs with different magnetic field strengths have different effects on osteoblast proliferation and differentiation [ 48 ].…”
Section: Effects Of Static Magnetic Fields On Bone Remodelingmentioning
confidence: 99%
“…According to the strength of the magnetic field, SMF can be classified as a hypomagnetic field (HyMF, <5 μT, commonly found in outer space), weak SMF (5 μT–1 mT, such as a geomagnetic field), moderate SMF (1 mT–1 T, such as common permanent magnets), and high SMF (>1 T, such as MRI and superconducting magnet) [ 47 ]. Numerous studies have shown that SMFs with different magnetic field strengths have different effects on osteoblast proliferation and differentiation [ 48 ].…”
Section: Effects Of Static Magnetic Fields On Bone Remodelingmentioning
confidence: 99%
“…This result has been reported by other researchers using other biomaterials and cell types. Recent reports have also indicated that static magnetic stimulation can induce viability and osteogenesis both in vitro and in vivo [ 52 ]. Based on our results, we hypothesized that magnetic stimulation disrupted the arrangement of cellular membranes, influencing cellular adhesion and attachment and, as a result, increasing the secretion of osteogenesis-related markers.…”
Section: Resultsmentioning
confidence: 99%
“…Magnetic fields have traditionally been implicated to support the natural process of bone regeneration, particularly with respect to fracture healing [7,8]. Recently, accumulating evidence has provided insights into how static magnetic fields from permanent magnets and Materials 2023, 16, 1846 2 of 11 pulsed electromagnetic fields affect the process of osseointegration of dental implants [9,10]. For instance, magnetic flux may stimulate osseointegration by increasing blood circulation and consequently enhancing the supply of oxygen and nutrients or by modulating cellular activity and signaling pathways (e.g., Wnt, MAPK signaling) relevant to bone formation [9,10].…”
Section: Introductionmentioning
confidence: 99%